Immunological Biomarkers and Epidemiological Evaluation of Lymphatic Filariasis Elimination Efforts in Osun State, Nigeria - Nzekwe Samuel C; Babarinde Samuel O.; Morakinyo Adetoun E.; Boladale Abiodun L.; Adeyemo Tolulope A.; Kehinde Damilale O.; Adeyemo Temitayo A.; Ogundinmu Marvelous O.; Oyebamiji David A.; Oladunni Opeyemi; Okorie Anyaele O.; Adejumobi Musibau O.; et al. (International Journal of Tropical Medicines, 2026)
Lymphatic filariasis (LF) remains a neglected tropical disease affecting millions globally, despite extensive elimination efforts. While the interruption of transmission is a key goal, the long-term immunological effects on individuals with existing complications like elephantiasis remain poorly understood. This study assessed the current transmission status of LF and the haematological profiles of infected individuals across selected Local Government Areas (LGAs) in Osun State, Nigeria. A total of 7,388 individuals from 12 LGAs were screened for circulating filarial antigen (CFA) using Abbott Filarial Test Strips (FTS). Additionally, haematological parameters, including white blood cells (WBCs), lymphocytes, monocytes, neutrophils, and eosinophils, were evaluated in five previously diagnosed LF patients to determine immune cell modulation associated with chronic infection. The pre-transmission assessment survey (pre-TAS) yielded a 0% antigenemia rate across all 12 LGAs, which falls within the WHO threshold (< 2%) for the cessation of mass drug administration (MDA). This indicates probable interruption of LF transmission in Osun State. Data from the community survey also revealed moderate compliance with preventive measures, with 41.09% of participants reporting sleeping under long-lasting insecticide-treated nets (LLINs), and 56.09% reporting participation MDA. Haematological assessments revealed significant variations in immune cell profiles among the LF patients. While some exhibited a reduction in WBCs, lymphocytes, suggestive of immune suppression, others displayed elevated counts consistent with active immune response or recovery. Persistent monocytosis and eosinophil reduction were common, indicating ongoing immune modulation despite parasite clearance. It is concluded that Osun State has entered the post-transmission phase of LF elimination, reflecting the effectiveness of sustained MDA and vector control interventions. Nonetheless, continued immune monitoring, post-MDA surveillance, and improved LLIN usage are essential to prevent reinfection and ensure lasting elimination.
Keywords: Lymphatic Filariasis; circulating filarial antigen; immune cells; mass drug administration, post-elimination surveillance